The Trees: A Collateral Victim of War: An Ecopoetic View - Sarmatha, S. (University of Jaffna, Sri Lanka, 2016)
This study examines ecological emphasis on trees as the collateral victim of war and the human empathy towards Nature. Unlike the English romantic poets; John Keats, Percy Bysshe Shelly, William Wordsworth and Samuel Taylor Coleridge, who spotlighted nature in the aesthetic perspective, the modern poets all over the world have confronted natural disaster, environmental injustice of War, the difficulties and challenges of urbanization and the impact of technological development, the aim of this paper is to focus on the environmental threat caused by war and the reciprocal relationship between humans and trees and to analyze the poems such as Aharon Shabtai’s The Trees are weeping, Derise Levertov’s In California during the Gulf War, Mullai Musrifa’s The story of the Tree, Auvvai’s Crossing the limits, S.Pathmanathan’s (Sopa) Thoughts on a Full Moon Day and John Clare’s All nature has a feeling in eco-poetic perspective. The poems discussed in this paper are written by the authors who belong to different countries. For instance, Aharon Shabtai who is an Israeli poet and translator wrote about his country’s plight aftermath of war in ecological perspective. Likewise, the writers such as Mullai Musrifa, S.Pathmanathan’s (Sopa) disclose the environmental calamity of war. This study traces the theoretical perspective of man-environment relations. The logical argument is constructed upon the interrelated themes of the poems. The approach used in this study is Ecocriticism that investigates underlying ecological value in the literary texts. The methodology used in this study includes analytical and descriptive methodology. This paper examines human empathy towards trees during the hazardous situation of war in the past.
Keywords: Eco-poetic; Ecological concern; Environmental injustice; Human’s empathy